ADAPTIVE VIDEO CONFERENCE SYSTEM ON A LOW BIT RATE NETWORK (Journal of Engineering, 2008)
This paper studies video conference system over low bit rate network. As a result of this study, some ideas are employed to transfer video and audio information through the dial up network with minimum jerky views, discontinuous voice and with a reasonable number of users. A video conference standard, which contains video standard and audio standard, is chosen to build a developed Video Conference System that takes into consideration the monitoring of the network load, by using a special designed sensor, called Network Load Sensor. The NLS is built to sense the network load. Based on the test results, the video resolution and audio compression ratio vary continuously. The system is implemented using visual C++, with using of sockets programming as the interface between clients and the conference server and the use of the Windows Multimedia Platform SDK, which support some audiovisual functions.